L’anthroposystème viticole en Haute-Saône : comprendre la place d’un paysage entre marginalité et inscription territoriale - Sylvain Estager (Projets de Paysage)
Wine-producing has quite disappeared nowadays in Haute-Saône whereas it once represented a culture of great importance. But a lot of vine manifestations are still remaining among those landscapes. To question those manifestations we need to study the landscape with a particular approach : we have to integrate some acute, inconspicuous components and dynamics linked to their existence. That’s why we use the anthroposystemic concept applied to all vine subject’s marks.